Atomically Thin Mesoporous In2O3–x/In2S3 Lateral Heterostructures Enabling Robust Broadband‐Light Photo‐Electrochemical Water Splitting. Issue 9 (18th December 2017) - Hou, Jungang; Cao, Shuyan; Sun, Yiqing; Wu, Yunzhen; Liang, Fei; Lin, Zheshuai; Sun, Licheng
Abstract: Atomically thin 2D heterostructures have opened new realms in electronic and optoelectronic devices. Herein, 2D lateral heterostructures of mesoporous In2 O3– x /In2 S3 atomic layers are synthesized through the in situ oxidation of In2 S3 atomic layers by an oxygen plasma‐induced strategy. Based on experimental observations and theoretical calculations, the prolonged charge carrier lifetime and increased electron density reveal the efficient photoexcited carrier transport and separation in the In2 O3– x /In2 S3 layers by interfacial bonding at the atomic level. As expected, the synergistic structural and electronic modulations of the In2 O3– x /In2 S3 layers generate a photocurrent of 1.28 mA cm −2 at 1.23 V versus a reversible hydrogen electrode, nearly 21 and 79 times higher than those of the In2 S3 atomic layers and bulk counterpart, respectively. Due to the large surface area, abundant active sites, broadband‐light harvesting ability, and effective charge transport pathways, the In2 O3– x /In2 S3 layers build efficient pathways for photoexcited charge in the 2D semiconductive channels, expediting charge transport and kinetic processes and enhancing the robust broadband‐light photo‐electrochemical water splitting performance. This work paves new avenues for the exploration and design of atomically thin 2D lateral heterostructures toward robust photo‐electrochemical applications and solar energy utilization. Abstract : Atomically thin 2D mesoporous In2 O3– x /In2 S3 lateral heterostructures are synthesized through the in situ oxidation of In2 S3 atomic layers. By virtue of large surface area, abundant active sites, broadband‐light harvesting ability, and effective charge transport pathways, the In2 O3– x /In2 S3 heterostructures build efficient charge transport pathways in 2D semiconductive channels, expediting charge transport and kinetic processes and enhancing robust broadband‐light photo‐electrochemical water splitting performance.